2020
DOI: 10.25122/jml-2019-0170
|View full text |Cite
|
Sign up to set email alerts
|

The Clinico-Epidemiological Profile of Patients with Gonorrhoea and Challenges in the Management of Neisseria gonorrhoeae Infection in an STI clinic, Ternopil, Ukraine (2013-2018)

Abstract: Gonorrhea is the second most common sexually transmitted infection spreading worldwide and a serious public health problem. How�ever, further data are required to improve the management of gonorrhea. Our aim was to review the features of gonococcal infection and characterize the challenges of its management. A retrospective descriptive study of the medical records of 136 adult patients with gonorrhea that visited Ternopil Regional Sexually Transmitted Infections Clinic (Ukraine) in 2013-2018 was performed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In this study, there are fewer MSM compared to heterosexual men, similar to the study from Ukraine. 13 This small number of cases of gonococcal urethritis in the MSM group could be caused by the location of gonorrhea infection which tends to be extragenital organs, as in a study in Lisbon which showed that of all gonorrhea diagnoses in the reported MSM group, the majority of cases occurred in extragenital organs, with the highest proportion at anorectal sites. 18 Nearly one-fifth of the patients in this study had used illicit drugs.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In this study, there are fewer MSM compared to heterosexual men, similar to the study from Ukraine. 13 This small number of cases of gonococcal urethritis in the MSM group could be caused by the location of gonorrhea infection which tends to be extragenital organs, as in a study in Lisbon which showed that of all gonorrhea diagnoses in the reported MSM group, the majority of cases occurred in extragenital organs, with the highest proportion at anorectal sites. 18 Nearly one-fifth of the patients in this study had used illicit drugs.…”
Section: Discussionmentioning
confidence: 84%
“…In this study, most of the patients were unmarried, consistent with research conducted in Ukraine and Ghana. 7,13 The incidence of gonorrhea in unmarried men is higher than in married men. This reflects riskier sexual behavior in unmarried men, such as changing sexual partners.…”
Section: Discussionmentioning
confidence: 99%
“…Boiko, I et al (2020) 7 showed the management of N. gonorrhoeae infection in Ukraine are the low level of examined females, asymptomatic infection in patients and sexual partners; disregarded testing of extragenital specimens, using of conventional laboratory tests (microscopy and culture) for screening and diagnostics of gonorrhea; deficient access to nucleic acid amplification tests in the public leading specialised STI clinics in Ukraine, low level of screening for HIV; low compliance of the follow-up visits; receiving questionable or even obsolete antimicrobial treatment. It is also supposed by our data that gonococcal infection is stigmatised.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the gonorrhea incidence increased during 2021 (Fig. 4K ), potentially due to its short incubation period 28 , which resulted in quick responses to PHSMs. In contrast, for diseases such as AIDS, syphilis, hepatitis C, and hepatitis B, which typically exhibit longer incubation periods (over a month) 29 , a substantial delay between symptom onset and reporting may occur.…”
Section: Discussionmentioning
confidence: 99%